Dancing Minghella Jonathan Lunn's Reading Room - Hutera, Donald (Dance Books Ltd., Alton,Hampshire (UK), 2008)
For the choreographer Jonathan Lunn, the actress Jutiet Stevenson and just about anyone who was a close friend or colleague of the late writer and Oscar-winning film director Anthony Minghella, Lunn's new touring production Reading Room is inevitably tinged with poignancy.